Design, health and innovation : co-design for improved cold chain compliance : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Lakomy, Sarah (Massey University, 2023)
Effective design approaches for multiple disciplinary collaborations are increasingly sought to benefit users and medical communities. This research seeks to develop effective explorative design research methods and identify their applicability to design teams operating in a hospital environment. This research is situated and trialled within the ‘Cold Chain – Quality Improvement’ project, which aims to improve the reliability of refrigerated pharmaceutical efficacy and the internal spatial management of pharmaceutical refrigerators. This is in order to reduce cold chain breaches, excursions, failures and subsequent wastage of valuable refrigerated pharmaceuticals. Further, the project is intended to support the ‘human factor’ in cold chain compliance, reducing performance pressure on staff who pack and access refrigerated medicines and vaccines. This consequently improves usability and reduces costs due to breaches, excursions, and failures. A combination of design research methods are employed; co-design workshop, semi-structured observations, iterative design developments, semi-structured interviews, and a pilot trial. These activities were used to inform communication across the design team, the broader research team, and stakeholder communities, along with end users to improve the focus and resolution of design activities. Within this process, design outputs are generated and assessed with regards to their valued experience to participants. This explorative and reflective design process has application to the ongoing larger project, and other emerging projects from the collaboration between Massey University and Te Whatu Ora, which seek approaches that enrich design research suitable for a hospital context.
Figures are reused with permission.
Keywords: 330309 Industrial and product design